2022
DOI: 10.1039/d2py00705c
|View full text |Cite
|
Sign up to set email alerts
|

Organic carboxylate salt-enabled alternative synthetic routes for bio-functional cyclic carbonates and aliphatic polycarbonates

Abstract: A cyclic carbonate with an ammonium carboxylate residue was found to serve as a nucleophile for esterification with alkyl bromides via the SN2 mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We have found that functional poly(trimethylene carbonate) (PTMC) analogues with methoxyalkyl ester side chains exhibit excellent antiplatelet properties. 19,20 These results further lead to the recent developments of ether-functionalized PTMC and polydioxanone. 21–23 However, biodegradation of the PTMC analogues proceeds slowly compared to that of aliphatic polyesters.…”
Section: Introductionmentioning
confidence: 82%
“…We have found that functional poly(trimethylene carbonate) (PTMC) analogues with methoxyalkyl ester side chains exhibit excellent antiplatelet properties. 19,20 These results further lead to the recent developments of ether-functionalized PTMC and polydioxanone. 21–23 However, biodegradation of the PTMC analogues proceeds slowly compared to that of aliphatic polyesters.…”
Section: Introductionmentioning
confidence: 82%
“…Investigations have been conducted on the use of CO 2 as a raw material in the synthesis of ureas, 28 organic carbonates, 29 carbamates, 30 and polycarbonates. [31][32][33] To synthesize aliphatic polycarbonates from CO 2 , four well-developed synthetic routes have been developed, including polycondensation of aliphatic diols with phosgene derivatives or dialkyl carbonates, 31 copolymerizations of CO 2 with epoxides, [34][35][36] direct polymerization of CO 2 , 33,[37][38][39] and ring-opening polymerization of cyclic carbonate monomers. 31,32,40 Conventionally, hazardous phosgene has been used as a raw material in industrial processes to prepare polycarbonates, which produce a lot of salt waste.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] To synthesize aliphatic polycarbonates from CO 2 , four well-developed synthetic routes have been developed, including polycondensation of aliphatic diols with phosgene derivatives or dialkyl carbonates, 31 copolymerizations of CO 2 with epoxides, [34][35][36] direct polymerization of CO 2 , 33,[37][38][39] and ring-opening polymerization of cyclic carbonate monomers. 31,32,40 Conventionally, hazardous phosgene has been used as a raw material in industrial processes to prepare polycarbonates, which produce a lot of salt waste. 37 Although copolymerization of epoxides or oxetanes with CO 2 has been investigated, direct polymerization from CO 2 as a carbonyl source will be ideal.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Larger ring cyclic carbonates such as 6MCCs over time have become popular monomers but are often prepared using harmful and low-atom economy reagents such as phosgene and its derivatives (Scheme 1a). 9…”
mentioning
confidence: 99%
“…7,8 Larger ring cyclic carbonates such as 6MCCs over time have become popular monomers but are often prepared using harmful and low-atom economy reagents such as phosgene and its derivatives (Scheme 1a). 9 Our group recently reported a simple catalytic CO 2 -based approach towards bicyclic 6MCCs (Scheme 1b). 10,11 This approach benefits from a double and cooperative activation strategy with a pendent alcohol group activating CO 2 while an Al-complex promotes intramolecular ring-opening of the oxirane in the substrate through coordination.…”
mentioning
confidence: 99%